Alteração da complacência intracraniana em paciente com doença renal crônica e diabetes mellitus T1: um relato de caso (Research, Society and Development, 2022)
Objective: The aim of this study was to relate the clinical profile with data on blood pressure (BP), intracranial pressure (ICP) and laboratory tests of a patient with Diabetes mellitus (DM) type 1 and chronic kidney disease (CKD) stage 5. Methodology: The research was carried out at the renal replacement therapy outpatient clinic of the Santa Casa de Misericórdia hospital, in Ponta Grossa-PR, previously approved by the ethics committee, under opinion nº 4,039,453. ICP monitoring and BP measurement were performed twice, on follow-up consultation days, in February and September 2020. In addition to the aforementioned parameters, a questionnaire on the patient's habits and demographic data was applied, and a consultation was carried out with the patient medical record for the collection of laboratory test data. Results: From February to September, the volunteer presented with persistent Systemic Arterial Hypertension (SAH) and hyperglycemia, and worsening of laboratory parameters. In February, the ICP morphology showed a significant change, suggesting intracranial hypertension, and the patient had a great impairment of visual acuity. In September, despite the worsening of the health condition, there was a significant improvement in vision and, also, an improvement in the ICP parameters, approaching normality. Between consultations, the diuretic administered by the patient was replaced. Conclusion: it is suggested that the visual impairment is due to intracranial hypertension and the improvement of both is related to the replacement of hydrochlorothiazide by furosemide, which occurred between consultations.